Water, sanitation, and depressive symptoms in Indonesia: The mediating role of life satisfaction - Mashita Fajri; Sri Idaiani; Amy Blakemore; Jonathan Gibson; Herni Susanti; Helen Brooks; Penny Bee; Asri Maharani (PLoS ONE, 2026)
Access to clean water and adequate sanitation is vital for public health. However, the effects of water and sanitation on depressive symptoms remain insufficiently explored among the general population in low- and middle-income countries (LMICs). This study aims to examine the links between sanitation conditions and depressive symptoms, and to evaluate the mediating role of life satisfaction (LS) among adults in Indonesia. We used the fifth wave of the Indonesian Family Life Survey (IFLS-5) dataset with participants aged 15 and above (mean: 37.32 years; SD: 14.93), collected in September 2014/March 2015. Depressive symptoms were measured using the CES-D-10 scale. Five sanitation indicators were included: drinking water, water source, toilet facilities, liquid waste disposal and safe waste disposal methods. Structural equation modelling (SEM) was employed to estimate the direct and indirect pathways linking sanitation factors and depressive symptoms through LS, adjusting for age and sex. The study involved 31,446 participants, of whom 7,312 (23%) were classified as having depressive symptoms. In the first SEM model, drinking water (β = 0.023, p < 0.001), water source (β = 0.033, p < 0.001), toilet facilities (β = 0.039, p < 0.001), sewage disposal (β = 0.027, p < 0.001) and waste disposal method (β = 0.021, p < 0.005) were directly associated with depressive symptoms. In the second SEM model, which included LS as a mediator, the direct effects remained consistent: drinking water (β = 0.013, p < 0.05), water source (β = 0.054, p < 0.001), toilet facilities (β = 0.068, p < 0.001), sewage disposal (β = 0.022, p < 0.001) and waste disposal method (β = 0.046, p < 0.001). Additionally, unimproved sanitation was significantly linked to lower LS and LS was strongly associated with depressive symptoms across all sanitation factors (β ≈ 0.124–0.126, p < 0.001). Poor water and sanitation are associated with a higher risk of depressive symptoms among Indonesian adults, with LS as a partial mediator of this relationship. These findings highlight the need to incorporate water and sanitation improvements into national mental health and public health policies.